Ensuring the effect of the res judicata principle in commercial court proceedings in conditions of open access to court decisions - Pilkov, Konstantyn (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The author argues that open access to full texts of judgments of the courts of Ukraine, provided by the Unified state register of court decisions, dictates the need for re-evaluation of the established views on the effective application of the res judicata principle in the aspect of ensuring that courts do not allow re-examination of finally resolved disputes in new, but identical proceedings. The article aims to use as an example the commercial court proceedings in order to reveal the legal fundament for imposing the duty to establish the existence of a res judicata judgement issued in an earlier identical proceeding upon the court or an interested party, in particular in the conditions of digitization of the judicial decision-making. According to the conclusions of the article, the party to the proceedings remains an entity that bears the burden of negative consequences of failing to reveal the existence of a final judgement in an identical case. It is worth to emphasize, that the fact-finding court is obliged to react to a party's statement of the existence of a res judicata decision and cannot place the burden of proving the existence of that decision on the party, but instead has the duty to determine this issue by way of obtaining a copy of the respective judgement upon the respective party's statement. At the same time, the court has the right, but is not obliged, to establish sua sponte the existence of a final court decision in identical proceedings. The author comes to the conclusion that the ongoing digitization of domestic court proceedings should open the opportunity for courts to automatically detect final judgments in the Register in order to identify potentially identical cases and provide the respective court with sufficient data for prompt reaction to attempts to initiate new proceedings aimed at re-examination of already decided cases.